2010
DOI: 10.1364/oe.19.000001
|View full text |Cite
|
Sign up to set email alerts
|

Over 1 hour continuous-wave operation of photonic crystal lasers

Abstract: We report on the long lifetime (>1 hour) of photonic crystal (PC) lasers under continuous-wave (CW) operation. For stable CW operation, we van-der-Waals-bonded our PC lasers to a novel submount structure consisting of MgF2-diamond bilayers on silicon substrate, which simultaneously ensures vertical mode confinement and efficient heat spread/dissipation. The combination of a Γ-point band-edge mode and butt-end fiber coupling yielded high CW fiber-coupled output power (~200 μW). The results demonstrate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Tattooing is based on the van der Waals bonding that is a versatile and reliable way to yield a seamless interface between two different material systems. [ 28–30 ] The SNF layer was directly contacted to the skin and therefore it could separate the CNT layer from the skin. This could protect the skin from possible harms by the CNT electrode such as electrical current and direct exposure to CNTs, along with skin‐compatible and functionable properties.…”
Section: Resultsmentioning
confidence: 99%
“…Tattooing is based on the van der Waals bonding that is a versatile and reliable way to yield a seamless interface between two different material systems. [ 28–30 ] The SNF layer was directly contacted to the skin and therefore it could separate the CNT layer from the skin. This could protect the skin from possible harms by the CNT electrode such as electrical current and direct exposure to CNTs, along with skin‐compatible and functionable properties.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the skin‐tattooing is achieved via the van der Waals bonding that is an adaptable and reliable method to realize the conformal interface between the materials. [ 40,41 ] After use, the E‐tattoos can be removed with water due to the weakening in the physical bond between tattoo and skin.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated that co‐extruded multilayer polymers promise to be an easily mass‐produced laser material offering advantages over corrugated grating‐based DFB lasers due to the large area available for lasing, flexibility and ease of manipulation, and wide range of mechanisms available for tuning the output. Further work will be needed to achieve some of the performance characteristics that have been demonstrated in long‐studied corrugated grating‐based DFB lasers such as low thresholds, extended operation, and the use of microchip lasers or even LEDs as pump sources. Further improvements in tunability and extended operation are possible with improved dyes and/or quantum dot emissive sources …”
Section: Prospects and Promisesmentioning
confidence: 99%